2020
DOI: 10.12740/app/111728
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of a change in attitude towards sexuality in medical students after their three years in medical college

Abstract: Aim of the studySexual health is central to holistic health care; studies indicate that health professionals are uncomfortable raising sexual issues partly because of their conservative sexual attitude. India hosts a multitude of social beliefs and cultural traditions. Everybody including Health professionals have certain beliefs hardwired into their mindsets, including attitude towards sexuality. so we aim to study the change in students’ attitude towards various aspects of own and others-sexuality & to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Most studies concerned with the relationship between gender and sexual attitudes have focused on people with a heterosexual orientation (e.g., Dosch et al, 2016;Sierra et al, 2021) or have not controlled for sexual orientation (e.g., Ojo, 2014;Shah et al, 2020). In addition, many have used measures of general sexual attitudes (e.g., García-Vega et al, 2017;Swami et al, 2017), which have more difficulty in predicting sexual behaviors (Blanc et al, 2018b) and sexual health (Sierra et al, 2021) than measures of attitudes toward specific sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies concerned with the relationship between gender and sexual attitudes have focused on people with a heterosexual orientation (e.g., Dosch et al, 2016;Sierra et al, 2021) or have not controlled for sexual orientation (e.g., Ojo, 2014;Shah et al, 2020). In addition, many have used measures of general sexual attitudes (e.g., García-Vega et al, 2017;Swami et al, 2017), which have more difficulty in predicting sexual behaviors (Blanc et al, 2018b) and sexual health (Sierra et al, 2021) than measures of attitudes toward specific sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have analyzed differences between men and women in sexual attitudes have focused on heterosexual individuals (e.g., Dosch et al, 2016;Sierra et al, 2021) or have not controlled for sexual orientation (e.g., Ojo, 2014;Shah et al, 2020). Recent studies conducted in United States (Lentz & Zaikman, 2021;Leri & DelPriore, 2021) and Portugal (Silva et al, 2021) examining the effect of sexual orientation on sexual attitudes in women from the general population and young adults show that nonheterosexual women have more permissive sexual attitudes than heterosexual women.…”
Section: Introductionmentioning
confidence: 99%
“…49 La consejería en sexualidad al paciente y su pareja debería hacer parte de la recuperación, 50 pero raramente se hace debido a la falta de experiencia o de comodidad en hablar de estos temas, así como el tiempo limitado por parte del personal médico. 51,52 Los factores asociados con la no discusión son el sexo femenino, la inactividad sexual previa, y la edad. 53 Las personas que reciben consejo tienen más alta frecuencia y satisfacción con la actividad sexual después del IAM, y reanudan la actividad sexual en un período de tiempo más corto 54,55 .…”
Section: Consideraciones Psicológicasunclassified
“…Therefore, establishing new sexual health education programs within Turkish nursing education is imperative (Yanıkkerem & Üstgörül, 2020). Although there are a few measuring sexual attitude and studies conducted in different groups, psychometric studies have been found with these and similar scales in samples such as nursing, social worker, and physiotherapy regarding the evaluation of sexual health (Areskoug-Josefsson et al, 2019;Blanc et al, 2018;Fino et al, 2018;Fisher et al, 2013;Gerbild et al, 2017;Shah et al, 2020). However, the nursing education in Turkey part of this scale has been decided that the most appropriate scale for students.…”
Section: Research-article20212021mentioning
confidence: 99%